A Practical Introduction to Hardware/Software Codesign - Schaumont, Patrick R. (Springer US : Imprint: Springer, 2010)
A Practical Introduction to Hardware/Software Codesign addresses the problem of combining software and hardware in a single system design process - such problems can be solved with hardware/software codesign. When used properly, hardware/software codesign improves the overall performance of digital systems, and it can shorten design time. The book covers four topics in hardware/software codesign: fundamentals, the design space of custom architectures, the hardware/software interface and application examples. The book comes with an associated design environment that helps the reader to perform experiments in hardware/software codesign. Each chapter also comes with exercises and further reading suggestions. A Practical Introduction to Hardware/Software Codesign is a great resource for engineers and students.